Calculation of The Imaginary Part of Atomic Form Factor For X-ray In Nickel - Ahmed Raheem Ahmed; Muhsin Hasan Ali (Tikrit Journal of Pure Science, 2019)
In the present study, we calculated the imaginary part of the x-ray scattering factor of nickel based on the principles of quantum mechanics to find a wave function that describes the electronic state of atoms by approximate methods, observed the study suggested that in both low energy values , and at high energy values , the imaginary part is approximately zero, this means that the electrons are intensely connected to the atom, where in the spectrum the photon energies are approximately equal to the electron bonding energy  we note the study pointed out that the imaginary part of the atomic scattering factor become  prominent and the electron becomes highly absorbent, the relative accuracy varies within range (0.03-0.22)%, and there was also a good agreement between the behavior we obtained for the imaginary part of the atomic scattering factor and the behavior that was calculated using other models.